Le corps du sultan ottoman - Nicolas Vatin (Revue des Mondes Musulmans et de la Méditerranée)
The sultan’s person is the keystone of the Ottoman Empire. Its very existence secures the world’s order. It is not surprising, then, that the Ottoman society never accepted the possibility of a break in the dynastic continuity, attaching a great importance to the physical presence of the monarch’s person. That’s why the living body of the sultan, if not exactly sacred, was nevertheless of a more than human nature, which superior value was more than symbolic and went beyond his own individual person.Consequently, when the sultan was dead or dethroned, he was nobody anymore and no special reverence was due to his physical person. On the contrary, while by dying he became in theory a Muslim as any other one, he had actually less rights than anybody else, precisely because he was an ancient monarch. His corpse could suffer degrading treatments dictated by political considerations: first of all, the rejection of any break in the dynastic continuity compelled more than once to keep secret the sultan’s death and to delay his burial for several weeks.Oner may nevertheless discern some elements of a sacralisation of the sultan’s dead body, and even some marks of a cult that could have developped. But such a cult probably was too much pagan to take root in the Ottoman State, which in the course of centuries tended to strengthen the orthodoxy of its practices and to give a growing importance to the dynasty, to the detriment of the person of individual sultans.